Okrucieństwo, przemoc i wychowanie według Michela de Montaigne’a. Szkic z deontologii pedagogicznej - Włodarczyk , Rafał (Studia Edukacyjne, 2017)
The aim of this paper is to analyze the phenomenon of cruelty according to deontology in education. The cruelty represents a significant threat to the pedagogical relationship for two reasons. Firstly, as one of the forms of aggression. Secondly, it occurs mostly in a hidden or covert form. The author refers to the concepts of cruelty put forth by Michel de Montaigne and Judith N. Shklar. Indicating indicates the difference between cruelty and violence, he points out the measures to prevent the emergence of atrocities in education and everyday life.